Kidney injury molecule-1 is specifically expressed in cystically-transformed proximal tubules of the PKD/Mhm (cy/+) rat model of polycystic kidney disease - Gauer, Stefan; Gretz, Norbert; Hoffmann, Sigrid; Kränzlin, Bettina (International journal of molecular sciences, 2016)
Expression of kidney injury molecule-1 (Kim-1) is rapidly upregulated following tubular injury, constituting a biomarker for acute kidney damage. We examined the renal localization of Kim-1 expression in PKD/Mhm (polycystic kidney disease, Mannheim) (cy/+) rats (cy: mutated allel, +: wild type allel), an established model for autosomal dominant polycystic kidney disease, with chronic, mainly proximal tubulointerstitial alterations. For immunohistochemistry or Western blot analysis, kidneys of male adult heterozygously-affected (cy/+) and unaffected (+/+) littermates were perfusion-fixed or directly removed. Kim-1 expression was determined using peroxidase- or fluorescence-linked immunohistochemistry (alone or in combination with markers for tubule segments or differentiation). Compared to (+/+), only in (cy/+) kidneys, a chronic expression of Kim-1 could be detected by Western blot analysis, which was histologically confined to an apical cellular localization in areas of cystically-transformed proximal tubules with varying size and morphology, but not in distal tubular segments. Kim-1 was expressed by cystic epithelia exhibiting varying extents of dedifferentiation, as shown by double labeling with aquaporin-1, vimentin or osteopontin, yielding partial cellular coexpression. In this model, in contrast to other known molecules indicating renal injury and/or repair mechanisms, the chronic renal expression of Kim-1 is strictly confined to proximal cysts. Its exact role in interfering with tubulo-interstitial alterations in polycystic kidney disease warrants future investigations.
Gesehen am 17.06.2019